2009
DOI: 10.1016/j.ajhg.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

DYNC2H1 Mutations Cause Asphyxiating Thoracic Dystrophy and Short Rib-Polydactyly Syndrome, Type III

Abstract: Jeune asphyxiating thoracic dystrophy (ATD) is an autosomal-recessive chondrodysplasia characterized by short ribs and a narrow thorax, short long bones, inconstant polydactyly, and trident acetabular roof. ATD is closely related to the short rib polydactyly syndrome (SRP) type III, which is a more severe condition characterized by early prenatal expression and lethality and variable malformations. We first excluded IFT80 in a series of 26 fetuses and children belonging to 14 families diagnosed with either ATD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
205
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(218 citation statements)
references
References 15 publications
11
205
0
2
Order By: Relevance
“…4F) and were also able to exclude cd28 (supplementary material Table S3D). Because mutations in DYNC2H1 cause thoracic dysplasia and ciliary defects in humans (Dagoneau et al, 2009;Merrill et al, 2009;El Hokayem et al, 2012;Schmidts et al, 2013) we first confirmed the nonsense mutation by sequencing single WT and homozygous aa65.6 pd1086 mutant larvae (Fig. 4G).…”
Section: Research Reportmentioning
confidence: 69%
“…4F) and were also able to exclude cd28 (supplementary material Table S3D). Because mutations in DYNC2H1 cause thoracic dysplasia and ciliary defects in humans (Dagoneau et al, 2009;Merrill et al, 2009;El Hokayem et al, 2012;Schmidts et al, 2013) we first confirmed the nonsense mutation by sequencing single WT and homozygous aa65.6 pd1086 mutant larvae (Fig. 4G).…”
Section: Research Reportmentioning
confidence: 69%
“…Dagoneau et al (2009) Okamoto et al (2015) identified compound heterozygosity for mutations c.5682_5683delAA and c.9070C > T in exons 37 and 57, respectively, of the DYNC2H1 gene in a fetus with SRPS3. Mei et al (2015) identified compound heterozygosity for mutations c.1151C > T and c.4351C > T in exons 8 and 28, respectively, of the DYNC2H1 gene in a fetus with SRPS3.…”
Section: Discussionmentioning
confidence: 99%
“…Among the five families, children in three were diagnosed with JATD, and in two of the families pregnancies were terminated for SRP type III. These data showed that JATD and SRP type III are variants of a single disorder belonging to the ciliopathy group (Dagoneau et al, 2009). Subsequently, additional DYNC2H1 mutations were identified as a common cause of JATD without major polydactyly, renal, or retinal involvement and one more case of compound heterozygous mutations in DYNC2H1 was shown to cause the typical SRP III phenotype (Okamoto et al, 2014).…”
Section: In Vitro Studies On Ift Dyneinmentioning
confidence: 95%